(untitled) (JURNAL ULET (Utility, Earning and Tax), 2024)
This study aims to find out the factors that affect customer loyalty, namely PT Bank Rakyat Indonesia and PT Bank Papua in Asmat Regency. The data collected in this study is qualitative data in the form of opinions/statements from PT Bank Rakyat Indonesia and PT Bank Papua in the form of questionnaires. The data analysis in this study used multiple linear regression. From the results of the analysis that has been carried out, it is found that the quality of service, trust and product quality are factors that affect customer loyalty, there are PT Bank Rakyat Indonesia and PT Bank Papua Asmat Regency. Thus, the most influential and significant factor is product trust and quality.